MIDWIFE ANTENATAL CARE QUALITY AS A DETERMINANT OF THE ACCURACY OF EARLY PRE-ECLAMPSIA DETECTION IN PRIMARY HEALTHCARE FACILITIES - Mufida Dian Hardika; Rury Narulita Sari; Khusnul Lailatul Fitri (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Preeclampsia remains an important contributor to maternal mortality and requires early detection through quality Antenatal Care (ANC). This study aimed to analyze midwives' ANC quality as a determinant of early preeclampsia detection accuracy in primary care facilities. A quantitative analytical cross-sectional design was used. The sample consisted of 30 midwives in Madiun Regency selected by total sampling. The instrument was valid, with r values ranging from 0.374 to 0.861 ( r table 0.361), and reliable with Cronbach's alpha of 0.882. Data were analyzed using Pearson correlation and simple linear regression. ANC quality was significantly related to early preeclampsia detection accuracy (r = 0.61; p = 0.001), with beta = 0.527 (p = 0.002) and R² = 0.31. ANC quality is a significant determinant of early preeclampsia detection accuracy in primary care facilities.